(untitled) (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2023)
The pedagogue has to solve many difficulties in educating stage artists. This is to reveal the unique creative aspects of each student, to increase their activity, to awaken and develop the ability to express themselves, to open their creative impressions, and to form a deep and artistic perception of reality. At the same time, it is to enrich their worldviews, expand their knowledge, and at the same time instill the basics of acting techniques